Eosinophilic sigmoiditis as a manifestation of severe gastrointestinal salmonellosis in children (clinical case) - Nezgoda, Iryna; Naumenko, Olha; Demchyshyn, Yaroslav; Onofriichuk, Olena; Starynets, Liudmila (ScienceRise: Medical Science, 2025)
Salmonellosis in children represents a significant medical and social problem due to its high incidence and the emergence of multidrug-resistant Salmonella strains. Objective. To analyze a clinical case of severe intestinal involvement in the gastrointestinal form of salmonellosis in a child. Materials and Methods. A clinical case of successful treatment of a 4-year-old child with severe intestinal involvement caused by the gastrointestinal form of salmonellosis due to a multidrug-resistant strain of Salmonella enteritidis is presented. A stepwise diagnostic approach and the rationale for selecting appropriate antibacterial therapy are described. Case Presentation. This report describes a case of gastrointestinal salmonellosis caused by Salmonella enteritidis in a 4-year-old child. The disease had a gradual onset, presented with abdominal pain and diarrhea with mucus and blood, without fever or vomiting. Physical examination revealed moderate dehydration, periumbilical tenderness, and hepatomegaly. Laboratory findings showed leukocytosis, accelerated erythrocyte sedimentation rate (ESR), and eosinophilia. Coprological examination revealed erythrocytes, leukocytes, and neutral fat. Elevated fecal calprotectin levels and decreased fecal elastase were detected. Immunological assessment demonstrated increased IgE levels and reduced cytotoxic T lymphocytes. Endoscopic and histological examinations confirmed active eosinophilic sigmoiditis. Stool culture identified a multidrug-resistant Salmonella enteritidis strain; only fourth-generation cephalosporins were effective, resulting in complete clinical recovery. Results and Discussion. The clinical presentation combined typical features of the gastrointestinal form of salmonellosis — bloody diarrhea, abdominal pain, hepatomegaly, and inflammatory changes in the complete blood count — with atypical manifestations, including the absence of vomiting and hyperthermia, eosinophilia, and IgE-mediated hypersensitivity. This constellation of findings suggests a mixed infectious–allergic disease course. Additionally, diagnostic markers of intestinal inflammation were identified, including a 2.6-fold increase in fecal calprotectin levels compared to age-adjusted reference values, which was corroborated by histological evidence of active intestinal inflammation in the form of eosinophilic sigmoiditis. Reduced fecal elastase levels indicated exocrine pancreatic dysfunction. An individualized therapeutic approach was applied based on antimicrobial susceptibility testing, which demonstrated multidrug resistance of the isolated Salmonella enteritidis strain. Fourth-generation cephalosporins proved to be effective in this case. Conclusions. This case illustrates the potential development of eosinophilic sigmoiditis in children with severe salmonellosis and highlights the importance of an individualized approach to antibacterial therapy, taking antimicrobial resistance patterns into account